Kepentingan India Melalui Act East Policy di Kawasan Asia Tenggara - Putri Ayu, Delvina; Muhammad Yusra; Anggraini Austin, Diah (Palito, 2024)
The end of the Cold War put India in a state of crisis therefore in 1991 India issued the Look East Policy. This policy brought India to significant progress in their country. However, the dynamic of international politics led India to make a change in this policy in 2014 to Act East Policy. The difference from this policy lies in the reach of the region and the reach of the field of cooperation. Nevertheless, India has always designated the Southeast Asian region as an anchor in its policies. This study aims to describe and analyze India's interest in Act East Policy as its foreign policy in the Southeast Asian region using the conceptual framework of national interest by Donald E. Nuechterlein. This research divides India's national interests into four basic needs namely defense, economy, world order, and ideology interest. Data collection and analysis techniques are carried out with qualitative methods as well as analytical descriptive approaches. The research found that India's national interest in the Southeast Asian region through Act East Policy is to contain the rising China, build the economy in the Northeast region of India through Southeast Asia, maintain the stability of the global order, and proliferate India's ideology and values. Keywords: Act East Policy, Indian Foreign Policy, National Interest, North East Region India, Southeast Asia.